Farmer exchange visited and reflection on rice-prawn production Borei Chulsa and Traing district, Takeo province - Tuy, Sinak; Ouk, Hak; Sean, Vichet (WorldFish, 2024)
On September 26, 2024, 50 participants (14 females) joined a farmer exchange visit in Borei Chulsa and Traing Districts, Takeo Province, under the Asian Mega Deltas Initiative. Participants observed rice-prawn farming practices at model and experimental sites, learning about climate-resilient techniques and economic benefits. Discussions focused on aquaculture techniques, challenges, and future implementation plans. Farmers shared insights on fencing, water quality, predator management, and diversifying crops. Model farmer Min Chhon highlighted his success, earning $8,000–$10,000 per cycle. The event emphasized knowledge sharing, fostering business clusters, and building market linkages to promote sustainable rice-prawn systems.